Terapi Tertawa pada Lansia Penderita Hipertensi di Wilayah Kerja Puskesmas Biru Kabupaten Bone - Irawati Irawati; Mardiana Mardiana; Alfian Mas’ud (Universitas Kristen Indonesia Toraja, 2025)
Aging or getting old is a natural thing, which cannot be avoided and rejected by every living creature, including things that will happen to every human being. One of the most common diseases found in the elderly is hypertension, because age is one of the risk factors for hypertension because the arteries or blood vessels in the elderly tend to harden and lose their elasticity. This community service aims to provide information about laughter therapy as one of the non-pharmacologic therapies to lower blood pressure. Method: The implementation of this laughter therapy begins with an explanation of laughter therapy and is continued with a demonstration by team members after which all participants participate in carrying out laughter therapy. The implementation of laughter therapy begins with an explanation regarding laughter therapy and is continued with a demonstration by team members after which all participants take part in carrying out laughter therapy. When laughter therapy was given, there were changes in blood pressure, where 7 respondents (63.7%) of elderly people experienced a decrease in blood pressure, while 4 respondents (36.3%) of elderly people had stable blood pressure. The results of this community service can show that providing laughter therapy is effective in lowering blood pressure even though the implementation is short. The implementation of this therapy is easy to do by the elderly and is effective as a complementary therapy in treating hypertension.